2022
DOI: 10.1038/s41598-022-08228-7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring IgG against Mycobacterium tuberculosis proteins in an Asian elephant cured of tuberculosis that developed from long-term latency

Abstract: Tuberculosis (TB) is fatal in elephants, hence protecting elephants from TB is key not only in the conservation of this endangered animal, but also to prevent TB transmission from elephants to humans. Most human TB cases arise from long-term asymptomatic infections. Significant diagnostic challenges remain in the detection of both infection and disease development from latency in elephants due to their huge bodies. In this study, we assessed cryopreserved sera collected for over 16 years, from the first Japane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In a recent study, we reported undetectable levels of IgG against Ag85B in an elephant diagnosed with LTBI. However, this levels sharply increased right before TB onset, after the long-term latency 34 . It has been proven that increasing antibody levels can potentially track TB disease progression in asymptomatic humans infection 5 , 18 .…”
Section: Discussionmentioning
confidence: 90%
“…In a recent study, we reported undetectable levels of IgG against Ag85B in an elephant diagnosed with LTBI. However, this levels sharply increased right before TB onset, after the long-term latency 34 . It has been proven that increasing antibody levels can potentially track TB disease progression in asymptomatic humans infection 5 , 18 .…”
Section: Discussionmentioning
confidence: 90%
“…For expression of HBHA, the CDS of HBHA with the addition of an NdeI site at the N-terminus and 6XHistidine and Kpn1 sites at the C-terminus was synthesized ( Supplementary Figure 1 ), inserted into pSO-AMI and introduced into M. smegmatis . Recombinant M. smegmatis strains were incubated on Sauton media containing 10 µg/mL kanamycin; expression of recombinant MTB MDP-1 and HBHA was induced by addition of acetoamide at a final concentration of 0.2% and purified by His GraviTrap by a described method ( 40 ). All antigen stimulations were performed in the presence of anti-CD28 and anti-CD49d costimulators (0.3 µg/mL).…”
Section: Methodsmentioning
confidence: 99%